Role of soil perception and soil variability by smallholder farmers in the low adoption rates of extension packages in Central America - Delgado, Luciana; Stoorvogel, Jetse J. (Elsevier, 2022)
Food systems are under pressure to produce more food of higher quality while reducing the pressure on natural resources. Currently, land degradation is widespread, especially in areas with smallholder farming. Agricultural extension may help farmers to adopt sustainable practices. However, adoption rates of interventions are often low in smallholder farming. This paper carries out an ex-ante analysis to determine to what extent the perception of soil characteristics (land cover, slope, soil organic matter, surface stoniness, and texture) and soil variability (how much acid or basic is the soil, i.e., pH level, and level of electric conductivity-EC) limit adoption with the final goal to design better policies to crop productivity. Differences in the perception of soil characteristics and variability between farmers and agricultural specialists, may result in situations where technological packages arrive at farms that are not likely to adopt or do not arrive at farmers that are likely to adopt. This paper studies differences in perception of soil characteristics and soil variability between agricultural specialists and farmers. Smallholder farmers in Central America producing beans were found to have different perceptions of soil characteristics relative to agricultural specialists. In addition, soil variability was considerable. As a result, it is concluded that soil perception and soil variability are likely causes of low adoption rates. Reducing the information gap with respect to the real needs of farmers will make policies more effective, resulting in higher adoption rates of new technologies and increased productivity.